1993
DOI: 10.1111/j.1460-9568.1993.tb00484.x
|View full text |Cite
|
Sign up to set email alerts
|

Mediation of Thalamic Sensory Responses In Vivo by ACPD‐activated Excitatory Amino Acid Receptors

Abstract: The existence of the so-called metabotropic excitatory amino acid receptor has been known for some years. Various functions have been suggested for this receptor, but the lack of selective antagonists for (IS, 3R)-aminocyclopentane dicarboxylic acid (ACPD) has precluded the direct demonstration of a functional role for this receptor in synaptic processes. We describe here a specific antagonism of the excitatory responses of thalamic neurons to ACPD by two novel antagonists, and a parallel antagonism by these c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0
1

Year Published

1994
1994
2002
2002

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(19 citation statements)
references
References 20 publications
(26 reference statements)
3
15
0
1
Order By: Relevance
“…Thus, each of these phenylglycine compounds blocks the (1S,3R)-ACPD-induced depolarization of neonatal rat motoneurones in vitro Eaton et al, 1993b; and the excitation of rat thalamic neurones in vivo (Eaton et al, 1993a). Also, in neurones of the nucleus tractus solitarius (NTS) in the rat brain stem in vitro, these same three phenylglycines antagonize the depression of excitatory postsynaptic currents (e.p.s.cs), the depression of inhibitory postsynaptic currents (i.p.s.cs), the depression of muscimolinduced currents and the potentiation of (RS)-a-amino-3-hydroxy-5-methylisoxazole-4-propionic acid (AMPA)-induced currents that is effected in each case by (IS,3R)-ACPD (Glaum et al, 1993).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Thus, each of these phenylglycine compounds blocks the (1S,3R)-ACPD-induced depolarization of neonatal rat motoneurones in vitro Eaton et al, 1993b; and the excitation of rat thalamic neurones in vivo (Eaton et al, 1993a). Also, in neurones of the nucleus tractus solitarius (NTS) in the rat brain stem in vitro, these same three phenylglycines antagonize the depression of excitatory postsynaptic currents (e.p.s.cs), the depression of inhibitory postsynaptic currents (i.p.s.cs), the depression of muscimolinduced currents and the potentiation of (RS)-a-amino-3-hydroxy-5-methylisoxazole-4-propionic acid (AMPA)-induced currents that is effected in each case by (IS,3R)-ACPD (Glaum et al, 1993).…”
Section: Introductionmentioning
confidence: 95%
“…Also, in neurones of the nucleus tractus solitarius (NTS) in the rat brain stem in vitro, these same three phenylglycines antagonize the depression of excitatory postsynaptic currents (e.p.s.cs), the depression of inhibitory postsynaptic currents (i.p.s.cs), the depression of muscimolinduced currents and the potentiation of (RS)-a-amino-3-hydroxy-5-methylisoxazole-4-propionic acid (AMPA)-induced currents that is effected in each case by (IS,3R)-ACPD (Glaum et al, 1993). These three phenylglycines selectively block nociceptive responses in rat thalamic neurones in vivo, relative to non-nociceptive sensory responses (Eaton et al, 1993a;Salt et al, 1993), and MCPG has been reported to block the induction of both NMDA-receptor dependent and NMDA receptor-independent long-term potentiation (LTP) in rat hippocampal slices (Bashir et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…There seems to be little evidence for a contribution to sensory responses of additional glutamate receptors from in vitro physiological studies, even though experiments have been designed that have attempted to reveal roles for, for example, metabotropic glutamate receptors (Turner & Salt 1998). By contrast, the situation appears to differ in in vivo experiments, where there appear to be sensory responses that have a contribution from mGlu receptors, and it is prob- 2002) able that this re ects recruitment of additional circuitry, possibly corticothalamic inputs (see § 3) (Eaton et al 1993;Salt & Turner 1998b;Rivadulla et al 2002).…”
Section: Sensory Inputs To Thalamic Relay Nucleimentioning
confidence: 99%
“…At least eight mGluRs have been molecularly characterized, and these activate effectors via interactions with heterotrimeric G proteins (1). Thus, the mGluRs are important for neuromodulatory functions, although mGluRs clearly mediate transmission at the retinal photoreceptor-depolarizing bipolar cell synapse (2)(3)(4) and at certain thalamic sensory neurons (5).…”
mentioning
confidence: 99%